2000
DOI: 10.1046/j.1525-1594.2000.06352.x
|View full text |Cite
|
Sign up to set email alerts
|

Trace Metals' Abnormalities in Hemodialysis Patients: Relationship with Medications

Abstract: A multicenter collaborative study was performed to investigate the prevalence of abnormal blood contents of 6 trace metals, copper (Cu), zinc (Zn), aluminum (Al), lead (Pb), cadmium (Cd), and mercury (Hg), in hemodialysis (HD) patients and to analyze their relationship with the medications, such as CaCO3, Ca acetate, Al containing phosphate-binding agents, 1,25-dihydroxy vitD3, 1-hydroxy vitD3, and erythropoietin (EPO), as well as hematocrit level, by chi-square statistics. From 6 medical centers in Taiwan, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
47
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 16 publications
8
47
0
1
Order By: Relevance
“…Bing Chen et al, who studied the whole blood and the serum samples of Chinese stable chronic renal failure patients, haemodialysis patients, post-transplant patients and subjects with normal renal functions, found a low prevalence of the elevated lead levels (>200 µg/L) in the dialysis patients, which was similar to the findings of Su-Hui Lee et al, [9,10]. Ja-Liang Lin et al, studied the blood lead levels in 315 patients who were on chronic peritoneal dialysis in an 18-month prospective study.…”
Section: Discussionsupporting
confidence: 57%
“…Bing Chen et al, who studied the whole blood and the serum samples of Chinese stable chronic renal failure patients, haemodialysis patients, post-transplant patients and subjects with normal renal functions, found a low prevalence of the elevated lead levels (>200 µg/L) in the dialysis patients, which was similar to the findings of Su-Hui Lee et al, [9,10]. Ja-Liang Lin et al, studied the blood lead levels in 315 patients who were on chronic peritoneal dialysis in an 18-month prospective study.…”
Section: Discussionsupporting
confidence: 57%
“…Sharupskiene et al had also reported elevated blood cadmium levels in haemodialysis patients [34]. Su-Hui Lee et al, reported elevated cadmium levels in haemodialysis patients; 333 (73%) out of the 456 haemodialysis patients had high cadmium levels (>2.5 μg/L), and the mean concentration was 3.32 ± 1.49 μg/L [35].…”
Section: Resultsmentioning
confidence: 99%
“…7,8 The rate of zinc deficiency in patients with HD is about 40-78%. [9][10][11] In a prospective cohort study, the effects of oral zinc sulfate supplementation on serum CRP, erythrocyte sedimentation rate (ESR), and ferritin level in HD patients were studied. From 155 patients with endstage renal disease on HD in the outpatient HD unit, 41 patients with low Zn level (Zn < 70 μg/mL) and normal serum iron were included in the study.…”
Section: Dear Sirmentioning
confidence: 99%